p53-dependent G(1) arrest in 1st or 2nd cell cycle may protect human cancer cells from cell death after treatment with ionizing radiation and Chk1 inhibitors - Petersen, L; Hasvold, G; Lukáš, Jiří; Bártek, Jiří; Syljuasen, R.G (Cell proliferation, 2010)
OBJECTIVES: This study was performed to explore the strategy of combining Chk1 inhibitors with ionizing radiation (IR) to selectively target p53-deficient cancer cells. MATERIALS AND METHODS: Survival and cell cycle progression were measured in response to IR and the Chk1 inhibitors, UCN-01 and CEP-3891, in colon carcinoma HCT116 p53+/+ and p53-/- cells, and in osteosarcoma U2OS-VP16 cells with conditional expression of dominant-negative p53 (p53DD). RESULTS: Clonogenic survival was selectively reduced in HCT116 p53-/- compared to p53+/+ cells after treatment with UCN-01 and IR, and HCT116 p53+/+ cells also displayed strong p53-dependent G(1) arrest in the 1st cell cycle after IR. In contrast, clonogenic survival was affected similarly in U2OS-VP16 cells with and without expression of p53DD. However, death of U2OS-VP16 cells was p53 dependent as assessed by cell viability assay at 72 h, and this was associated with p53-dependent G(1) arrest in the 2nd cell cycle after treatment. Notably, HCT116 cells were overall more resistant than U2OS cells to cytotoxic effects of Chk1 inhibitors. CONCLUSION: Our results suggest that p53-dependent G(1) arrest in both 1st and 2nd cell cycles may protect human cancer cells from cell death after treatment with IR and Chk1 inhibitors. However, a challenge for future clinical use will be that different cancers display different intrinsic sensitivity to such inhibitors.
Keywords: Tumor Suppressor Protein p53; Nervous System Neoplasms; Radiation, Ionizing; Genes, p53; Staurosporine; HCT116 buňky; Cell Cycle; Neoplasms; nádory; nádory tračníku; geny p53; lidé; HCT116 Cells; proteinkinasy; ionizující záření; buněčná smrt; staurosporin; buněčný cyklus; Colonic Neoplasms; nádory nervového systému; Cell Death; nádorový supresorový protein p53; Protein Kinases; Cell Survival; viabilita buněk; Humans